The impact of an innovative education and outreach project - Barnett, R. Michael; Johansson, K. Erik (Frontiers in Physics, 2024)
In 1995, the ATLAS Experiment at the Large Hadron Collider embarked on an ambitious journey, driven by a passion to ignite curiosity and inspire future scientists. Our quest wasn't just about uncovering the universe's mysteries; it was a cosmic odyssey to share the thrill of scientific exploration with all. Our exploratory collection included engaging classroom activities, a dynamic website, captivating videos, a vibrant YouTube channel, global social media connections, and a captivating planetarium show, all intertwined with the exciting search for the elusive Higgs Boson. This scientific program celebrates the enduring curiosity of humanity and the passion that fuels discovery.